GANGGUAN PENGHIDU SEBAGAI FAKTOR RISIKO PENURUNAN FUNGSI KOGNITIF PADA LANSIA PENDIDIKAN RENDAH - Yuda Turana (NEURONA, 2019)
OLFACTORY IMPAIRMENT AS A RISK FACTOR OF COGNITIVE DECLINE IN THE ELDERLY WITH LOW EDUCATIONABSTRACTIntroduction: Olfactory function plays a role in cognitive decline. Olfactory disorders are known to predict faster cognitive decline and indicate nerve degeneration in the brain. Elderly people with lower assessment of olfactory function are associated with decreased memory function. While the elderly with low education are known to have a high risk of developing dementia. So far there has been no research on disorders of olfactory on cognitive function of elderly with low education.Aim: This study aimed to determine the role of olfactory function and other risk factors related to cognitive decline in the elderly with lower education.Method: A nested cohort study design was used in the fostered area of active age research (in the period 2015-2017) at North, West and Central Jakarta, in elderly with lower education. The cognitive function was assessed using the MMSE instrument. Subjects with a decrease of MMSE score more than 2 points compared to baseline were categorized as having cognitive decline. The olfactory assessment was tested using ten aromas that have been standardized, lipid profile, fasting glucose, and APOE were included.Results: There were 148 elderly subjects with lower education background, majority of the respondent was female 114 (77%) with mean of age 70.2±8.9 years old. Our study showed that 64 (43.2%) subjects had cognitive decline with a mean of decreased was -1.02±3.8 after a follow-up of 2 years, bivariate analyses showed smoking habit and olfactory impairment as a risk factor of cognitive decline (p<0.05; OR=3.1; OR=2.6). In multivariate analyses, subjects with olfactory impairment were 2,7 times more likely to have cognitive decline.Discussion: Olfactory disfunction is a risk factor for reduced cognitive function in the elderly with low education.Keywords: Cognitive, elderly, olfactoryABSTRAKPendahuluan: Fungsi penghidu berperan terhadap penurunan fungsi kognitif. Gangguan penghidu diketahui dapat memprediksi penurunan kognitif yang lebih cepat dan mengindikasikan degenerasi saraf di otak. Lansia dengan penilaian fungsi penghidu yang lebih rendah berkaitan dengan penurunan fungsi memori. Sementara lansia dengan pendidikan rendah diketahui mempunyai risiko tinggi terkena demensia. Sejauh ini belum ada penelitian tentang gangguan penghidu terhadap fungsi kognitif lansia berpendidikan rendah.Tujuan: Untuk mengetahui peranan fungsi penghidu dan faktor risiko lainnya terhadap penurunan fungsi kognitif pada lansia pendidikan rendah.Metode: Penelitian dengan desain nested cohort di wilayah binaan active ageing research (periode 2015-2017) yaitu di Jakarta Utara, Jakarta Barat, dan Jakarta Pusat pada lansia dengan pendidikan rendah. Pemeriksaan fungsi kognitif dinilai dengan menggunakan Mini Mental State Examination (MMSE). Subjek dengan penurunan skor MMSE lebih dari 2 poin dibandingkan baseline dikategorikan mengalami penurunan fungsi kognitif. Subjek dilakukan penilaian fungsi penghidu menggunakan 10 aroma yang telah distandarisasi, pemeriksaan profil lipid, gula darah puasa, dan APOE.Hasil: Didapatkan 148 subjek lansia berpendidikan rendah yang mayoritas perempuan (77%) dengan rerata usia 70,2±8,9 tahun. Sebanyak 43,2% lansia mengalami penurunan skor MMSE dengan rerata penurunan sebesar -1,02±3,8 pada pemantauan selama 2 tahun. Analisis bivariat menunjukkan perilaku merokok dan gangguan olfaktori memiliki risiko terhadap penurunan fungsi kognitif (RO=3,1dan RO=2,6; p<0,05). Analisis multivariat menunjukkan subjek dengan gangguan olfaktori memiliki risiko 2,7 kali untuk mengalami penurunan fungsi kognitif.Diskusi: Gangguan olfaktori merupakan faktor risiko penurunan fungsi kognitif pada lansia berpendidikan rendah.Kata kunci: Fungsi penghidu, kognitif, lansia, kognitif, olfaktori